RANCANG BANGUN APLIKASI MANAJEMEN TUGAS MENGGUNAKAN LARAVEL - Randi, Randi Afif (UNIVERSITAS STEKOM, 2025)
This research aims to develop a Task Management Application to assist lecturers in managing and monitoring student assignments. Currently, communication and coordination for assignments are conducted through platforms like WhatsApp, Google Meet, and Google Classroom, leading to challenges in task monitoring, execution, file storage, communication, and task management. These issues include ineffective group chats and a lack of information on ongoing or upcoming tasks. Using the Waterfall model methodology, the research focuses on creating an application that addresses these problems by providing task monitoring, a forum for student-lecturer communication, file storage, and a time schedule feature for project completion. The application is designed to facilitate better task management and improve the learning process for both lecturers and students.